Do sudden gains predict treatment outcome in social anxiety disorder? Findings from two randomized controlled trials. (October 2019) - Butler, Rachel M.; O'Day, Emily B.; Kaplan, Simona C.; Swee, Michaela B.; Horenstein, Arielle; Morrison, Amanda S.; Goldin, Philippe R.; Gross, James J.; Heimberg, Richard G.
Abstract: Objective: Sudden gains (SGs) have been found to occur during randomized controlled trials (RCTs) for social anxiety disorder (SAD). Evidence is mixed whether SGs relate to treatment outcome in SAD. We examined SGs in two RCTs for SAD. Method: Study 1 ( N = 68) examined SGs in individual cognitive-behavioral therapy (CBT), and Study 2 ( N = 100) compared SGs in group CBT and Mindfulness-Based Stress Reduction (MBSR). Weekly ratings of social anxiety were used to calculate SGs. The Liebowitz Social Anxiety Scale-Self-Report and the Social Interaction Anxiety Scale were completed at pretreatment, posttreatment, and follow-up to assess outcome. Results: In Study 1, 17.6% of participants experienced a SG. Participants with SGs started and ended treatment with lower social anxiety. SGs were not associated with greater decreases in social anxiety from pre-to posttreatment or 12-month follow-up. In Study 2, SGs occurred in 27% of participants and at comparable rates in MBSR and group CBT. SGs were not associated with changes in social anxiety during treatment in either condition. Conclusion: SGs occurred during treatment for SAD. In both RCTs, participants improved regardless of experiencing a SG, suggesting that SGs are not predictive of greater improvement during treatment for SAD. Highlights: Sudden gains are sudden, large improvements in symptom severity during treatment. We examined sudden gains in RCTs of CBT vs WL and CBGT vs MBSR vs WL for SAD. In Study 1, sudden gains were associated with lower SA at pre- and posttreatment. In Study 2, sudden gains occurred at similar rates and magnitude in CBGT and MBSR. Sudden gains did not predict pre-to posttreatment changes in SA in Study 1 or 2.